Phase II Trial of Erlotinib during and after Radiotherapy in Children with Newly Diagnosed High-Grade Gliomas - Qaddoumi, Ibrahim; Kocak, Mehmet; Pai-Panandiker, Atmaram S.; Armstrong, Gregory T.; Wetmore, Cynthia; Crawford, John R.; Lin, Tong; Boyett, James M.; Kun, Larry E.; Boop, Fredrick A.; Merchant, Thomas E.; Ellison, David W.; et al. (Frontiers in Oncology, 2014)
Background. Epidermal growth factor receptor is overexpressed in most pediatric high-grade gliomas (HGG). Since erlotinib had shown activity in adults with HGG, we conducted a phase II trial of erlotinib and local radiotherapy in children with newly diagnosed HGG. Methods. Following maximum surgical resection, patients between 3 and 21 years with nonmetastatic HGG received local radiotherapy at 59.4 Gy (54 Gy for spinal tumors and those with ≥70% brain involvement). Erlotinib started on day 1 of radiotherapy (120 mg/m2 per day) and continued for 2 years unless there was tumor progression or intolerable toxicities. The 2-year progression-free survival (PFS) was estimated for patients with intracranial anaplastic astrocytoma (AA) and glioblastoma. Results. Median age at diagnosis for 41 patients with intracranial tumors (21 with glioblastoma and 20 with AA) was 10.9 years (range, 3.3 to 19 years). The 2-year PFS for patients with AA and glioblastoma was 15% ± 7% and 19% ± 8%, respectively. Only five patients remained alive without tumor progression. Twenty-six patients had at least one grade 3 or 4 toxicity irrespective of association with erlotinib; only four required dose modifications. The main toxicities were gastrointestinal (n=11), dermatologic (n=5), and metabolic (n=4). One patient with gliomatosis cerebri who required prolonged corticosteroids died of septic shock associated with pancreatitis. Conclusions. Although therapy with erlotinib was mostly well tolerated, it did not change the poor outcome of our patients. Our results showed that erlotinib is not a promising medication in the treatment of children with intracranial AA and glioblastoma.